2010
DOI: 10.2174/1874612811003010057
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Neurocognition: Review of Evidence and Methodological Considerations

Abstract: The relationship between diet and cognitive function has been a topic of increasing interest, as numerous studies have shown that variations in dietary practices and nutrient intake are may protect against age-related cognitive decline, as well as the development of dementia and Alzheimer's Disease (AD). Various dietary practices and specific nutrient components of these diets have been examined in relation to cognitive performance including 1) dietary fatty acids (including fish oil) and the Mediterranean die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 57 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…These studies often focus on specific dietary elements and the role of fatty acids has received particularly close attention. For example, greater fish consumption and overall polyunsaturated fat intake has been associated with both improvements in cognition and reduced Alzheimer’s disease risk; conversely, high saturated and trans‐unsaturated fats are associated with worse cognition, greater decline and increased Alzheimer’s disease and vascular dementia risk [138].…”
Section: Lifestyle Modification: Strategies For Preventionmentioning
confidence: 99%
“…These studies often focus on specific dietary elements and the role of fatty acids has received particularly close attention. For example, greater fish consumption and overall polyunsaturated fat intake has been associated with both improvements in cognition and reduced Alzheimer’s disease risk; conversely, high saturated and trans‐unsaturated fats are associated with worse cognition, greater decline and increased Alzheimer’s disease and vascular dementia risk [138].…”
Section: Lifestyle Modification: Strategies For Preventionmentioning
confidence: 99%
“…Education level, physical activity, healthy dietary patterns (a diet which consists of fruits, vegetables, whole grains, and fish), abstinence from smoking, along with engagement in mental, social, and physical activities are protective measures against MCI [6]. Moreover, moderate calorie restriction may lead to healthy aging, extended lifespan, and improve metabolic and vascular parameters [7,8]. In addition to these conventional approaches, new intervention strategies can be introduced to aid in combating MCI.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have also been null findings, with recent systematic reviews reporting that evidence linking dietary patterns to ADRD outcomes remains inconclusive [113,151,152]. Importantly, although the MeDi and DASH were originally characterized for their beneficial impact on CVD risk factors and CVD outcomes, few studies have provided compelling evidence that the observed associations between dietary patterns and ADRD are mediated through vascular pathways, [148,153] with multiple, indirect mechanisms connecting dietary behaviors to cognitive outcomes [144,154].…”
Section: Dietary Patternsmentioning
confidence: 99%